Sticky-wage models and knowledge capital - Kevin X. D. Huang; Munechika Katayama; Mototsugu Shintanin; Takayuki Tsuruga (Osaka University, Institute of Social and Economic Research (ISER), 2019)
We present a sticky-wage model with two types of labors: while worker's labor contributes to current production, researcherís work helps develop new ideas to add to firm's knowledge capital that enhances its productivity for many periods. The long-lived effect of knowledge capital on productivity is analogous to the long-lasting effect of consumer durables on utility in the sticky-price model of Barsky, House and Kimball (2007). Our sticky-wage model generates the near monetary neutrality result similar to the result in their sticky-price model, if returns to researchers' labor are low in developing knowledge capital. We show, however, that the relative role of the pricing of the two production inputs analogous to consumption durables and nondurables in their sticky-price model is completely reversed in our sticky-wage model.
Keywords: E22; E24; E31; E52; 330; Intangible capital; wage rigidity; monetary policy